STRATEGI PENGELOLAAN ADMINISTRATIF DARI DAMPAK “BALLAST WATER” DI DAERAH BERKEMBANG UNTUK KEBERLANJUTAN KEHIDUPAN MASYARAKAT PESISIR - Mohamad Sayuti Djau (Publik : (Jurnal Ilmu Administrasi), 2015)
The purpose of the preparation from this article is to give describing of the impact of ballast water on the coastal environment and try to give a solution how the administrative management should be done to the sustainability of coastal society. The method used in writing of this article that is library research from a variety of sources and based on field observations in some areas with the activity of high boat traffic. Ballast water is sucked by the pump into the tank ship ballasts are used to maintain the stability of the ship during the cruise, generally consists of water mixed with various types of marine microorganisms, sediments and rocks. Marine microorganisms are carried on and switched via ship ballasts tanks will be able to survive in new waters, but life will change and tend to be predatory. This can cause damage to the food chain and the environment in new waters. Impact caused by Aquatic Invasive Species (AIS ) on ballast water, Hull and others form part of the ship of the ecological impact, economic and human health is a common concern this moment especially scientists, therefore need for appropriate methods in management. Some approaches a comprehensive strategy in the operational procedures ship, port, ship monitoring inspection, certification, training and education as well as the roles and responsibilities are clear of the implementing the regulation is an integral part in the effort to reduce the alien species.